The business of black beauty: social entrepreneurship or social injustice? - Phipps, Simone T.A.; Prieto, Leon C. (Journal of Management History, 2018)
Purpose This paper aims to examine the black beauty industry from a historical perspective and consider the fairness heuristic theory to determine if organisations in this industry are engaging in and promoting social entrepreneurship or contributing to social injustice. The paper explores the work of Annie Turnbo-Malone and Madame C.J. Walker, pioneers and stalwart entrepreneurs in the black beauty business, to discuss the controversial issue. Current and future applications are also investigated and presented. Design/methodology/approach Papers from earlier as well as more contemporary journals, news media and books were examined and synthesised to render a balanced view to aid in the entrepreneurship or injustice debate. Findings The paper concludes that decisions about fairness and justice involve perception and thus vary by individual, allowing a substantial case for the black beauty industry to both be commended for social entrepreneurship and condemned as a proponent of social injustice (distributive, procedural and interactional). Originality/value Organisations have substantial impact on individuals, groups, the community and society. A meaningful organisation encourages expression, perceptions of worth and constructive attitudes and behaviour, and refrains from reflecting excessive dictatorship or dehumanisation. This paper highlights both positive and negative organisational and societal issues concerning the business of black beauty, a relatively understudied topic in management in general and management history in particular, and it provides a unique lens from which to build awareness about entrepreneurship and justice and to effect needed change.
Keywords: Business History and race